Developmental changes in GABAergic mechanisms in human visual cortex across the lifespan - Pinto, Joshua G.; Hornby, Kyle R.; Jones, David G.; Murphy, Kathryn M. (Frontiers in Cellular Neuroscience, 2010)
Functional maturation of visual cortex is linked with dynamic changes in synaptic expression of GABAergic mechanisms. These include setting the excitation-inhibition balance required for experience-dependent plasticity, as well as, intracortical inhibition underlying development and aging of receptive field properties. Animal studies have shown developmental regulation of GABAergic mechanisms in visual cortex. In this study, we show for the first time how these mechanisms develop in the human visual cortex across the lifespan. We used Western blot analysis of postmortem tissue from human primary visual cortex (n=30, range: 20 days to 80 years) to quantify expression of 8 pre- and post-synaptic GABAergic markers. We quantified the inhibitory modulating cannabinoid receptor (CB1), GABA vesicular transporter (VGAT), GABA synthesizing enzymes (GAD65/GAD67), GABAA receptor anchoring protein (Gephyrin), and GABAA receptor subunits (GABAA∝1, GABAA∝2, GABAA∝3). We found a complex pattern of changes, many of which were prolonged and continued well into into the teen, young adult, and even older adult years. These included a monotonic increase or decrease (GABAA∝1, GABAA∝2), a biphasic increase then decrease (GAD65, Gephyrin), or multiple increases and decreases (VGAT, CB1) across the lifespan. Comparing the balances between the pre- and post-synaptic markers we found 3 main transitions (early childhood, early teen years, aging) when there were rapid switches in the composition of the GABAergic signaling system, indicating that functioning of the GABAergic system must change as the visual cortex develops and ages. Furthermore, these results provide key information for translating therapies developed in animal models into effective treatments for amblyopia in humans.